ANALYSIS OF THE EFFECT OF VOLUME FRACTION VARIATION ON TENSILE AND BENDING STRENGTH OF COMPOSITE FIBER COMBINATION OF PINEAPPLE LEAVES AND FIBERGLASS WITH POLYESTER RESIN MATRIX BY COMPRESSION MOLDING METHOD - Paundra, Fajar; Simatupang, Valentino Hasael; Muhyi, Abdul; Sidik, M. Farhan; Maulana, Sena (DINAMIKA : Jurnal Teknik Mesin, 2024)
Pineapple leaf fiber is a waste that is widely found on the island of Sumatra and its potential utilization has not been maximized. Pineapple leaf fiber has potential as a constituent of natural fiber composites. This study aims to determine the effect of volume fraction variation on tensile and bending strength reinforced with pineapple leaf fiber and fiberglass. The composite manufacturing process uses the compression molding method for 24 hours with a pressure of 50 bar and is given a variation of 70% polyester resin, 25% fiberglass, 20%, 15%, 10%, 5%, and 25%, 20%, 15%, 10%, 5% pineapple leaf fiber. After completion of the composite manufacture, density and porosity testing was carried out with ASTM C271 standards, tensile testing was carried out using D3930 standards and bending testing using D790 standards. The lowest density test results and the highest porosity in composites with 70% resin variation, 25% fiberglass, 5% pineapple leaf fiber with a value of 0.87 gr/cm3 - 7.80% and the highest density value and the lowest porosity with 70% resin variation, 5% fiberglass, 25% pineapple leaf fiber with a value of 1.81 gr/cm3 - 1.53%. The highest tensile strength test results in the variation of 5% fiberglass volume fraction 25% pineapple leaf fiber of 237.76 MPa, and the lowest value in the variation of 25% fiberglass volume fraction 5% pineapple leaf fiber of 98.37 MPa. And the highest bending test was obtained in the variation of the volume fraction of 5% fiberglass 25% pineapple leaf fiber at 332.14 MPa, and the lowest value was obtained in the variation of 25% fiberglass 5% pineapple leaf fiber at 194.95 MPa.